PENINGKATAN BERPIKIR KREATIF DAN HASIL BELAJAR FISIKA MELALUI PENDEKATAN CREATIVE PROBLEM SOLVING (CPS) - Bambang Subakir (Jurnal Pendidikan Fisika, 2013)
The objective in this research to describing implementation oflearning physics using the approach Creative Problem Solving (CPS) toimprove creative thinking skills and students’ achievement in class XI IPA-1SMA Harapan 3 Delitua. The research method applied is Classroom ActionResearch (CAR) through two learning cycles; each cycle consisted byplanning, implementation, observation and reflection. The results showedthat learning physics with CPS approach can improve students’ ability tothink creatively. After learning undertaken by the CPS approach increasedstudents ability to think creatively and achievement. This is evidenced by: (1) Increasing the number of students who pass out of 12 person in the first cycleto 29 person in the second cycle with an average of 77,39 learning outcomes.N-gain in the first cycle of 0.19 is included in the category of low-and N-gainin the second cycle of 0.30 is included in the medium category, (2) Activitygroup average student in the learning process are included in the categoryActivities Fair increased to High Activity category, and (3) The use ofcreative thinking of students in the first cycle an enough increased to a highin the second cycle. Creative thinking ability of students in teaching physicsto provide benefits in solving problems in the community.